2007
DOI: 10.1088/1475-7516/2007/11/030
|View full text |Cite
|
Sign up to set email alerts
|

Emergent universe in a Jordan–Brans–Dicke theory

Abstract: In this paper we study emergent universe model in the context of a self interacting Jordan-Brans-Dicke theory. The model presents a stable past eternal static solution which eventually enters a phase where the stability of this solution is broken leading to an inflationary period. We also establish constraints for the different parameters appearing in our model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 43 publications
(110 reference statements)
2
84
0
Order By: Relevance
“…Universe based on alternative theories to General Relativity, like Jordan-Brans-Dicke [68], which present stable past eternal static regime [19,20]. It is interesting explore this possibility because emergent universe models based on GR suffer from instabilities, associated with the instability of the Einstein static universe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universe based on alternative theories to General Relativity, like Jordan-Brans-Dicke [68], which present stable past eternal static regime [19,20]. It is interesting explore this possibility because emergent universe models based on GR suffer from instabilities, associated with the instability of the Einstein static universe.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting explore this possibility because emergent universe models based on GR suffer from instabilities, associated with the instability of the Einstein static universe. This instability is possible to cure by going away from GR, for example, by consider a Jordan Brans Dicke theory at the classical level, where it have been found that contrary to general relativity, a static universe could be stable, see [19,20]. Another possibility is considering non-perturbative quantum corrections of the Einstein field equations, either coming from a semiclassical state in the framework of loop quantum gravity [13,17] or braneworld cosmology with a timelike extra dimension [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, most simple models developed in a context of General Relativity suffer from instabilities, associated with the instability of Einstein's static universe [17]. On the other hand, Tensor-Scalar theories can give us the possibility to explore the viability of a stable UE model in which there is no initial singularity [19,18]. The theory normally associated with Scalar-Tensor models is the Jordan-Brans-Dicke (JBD) theory of gravitation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Gauss-Bonnet gravity as gravitational alternative for dark energy is however considered by Nojiri and Oddintsov [19]. It is also shown recently that EU model can be successfully implemented in Brane world gravity [20,21], Brans-Dicke theory [22]. A number of cosmological models are obtained with different cosmological fluids and fields [14,[23][24][25][26] where initial singularity problem is addressed.…”
Section: Introductionmentioning
confidence: 99%